Working Environment of Nurses in Two District Hospitals (Bangladesh Journal of Anatomy, 2011)
Context: The study was designed to see the working environment of nurses in two district hospitals. Study design: Cross sectional, descriptive type of study. Place and period of study: The study was carried out in National Institute of Preventive and Social Medicine (NIPSOM), Mohakhali, Dhaka from April to June, 2005. Methods: A total of 60 (sixty) nurses were selected by systematic random sampling method. Two District Hospitals were selected by Purposive Sampling. Data was collected by: face-to-face interview using a questionnaire consisting of both close ended and open ended questions. Results: Both positive and negative findings came out regarding working environment of the nurses. Conclusion: Some suggestions came out to improve the working environment of the nurses. Key words: Working environment; Nurses; District Hospitals. DOI: 10.3329/bja.v8i2.7022Bangladesh Journal of Anatomy July 2010, Vol. 8 No. 2 pp. 81-84